A Agenda 2030 para o desenvolvimento sustentável e o Brasil: uma análise da governança para a implementação entre 2015 e 2019 - Araújo, Ana Beatriz Arantes (2020)
This study conveys an analysis of the United Nations’ 2030 Agenda for Sustainable Development’s implementation governance by the Brazilian Government, between 2016 and 2019. It is argued that the agenda proposes a shift on the international cooperation’s paradigm with the adoption of a goal setting mechanism instead of a rule making one. To articulate the analysis, the agenda implications on governance and its parameters, with those from the literature are presented and discussed, with emphasis on Common, But Differentiated Governance and metagovernance (MEULEMAN e NIESTROY, 2015). It is also portrayed a trajectory of Brazilian participation on debates about environment and development, using as time frames the international conferences on the environment. In addition, it is analyzed the country’s experience with the adoption of former international agendas – the Agenda 21 and the Millennium Development Goals. Finally, it is developed an investigation of the National Commission on the Sustainable Development Goals, a consultative collegiate with the attribution to coordinate the 2030 Agenda’s implementation in Brazil. It was active between 2017 and 2019, when it was extinguished. As a part of the study, the work of the Brazilian Institute for Geography and Statistics (IBGE, in Portuguese) and of the National Institute for Advanced Economic Research (IPEA), as advisors for the commission, is presented, and complemented with a view of civil society’s participation in different moments of negotiation. Among the research sources are the documents found in primary data collecting on the government official archive, available online, meeting records and documents obtained with the National Secretariat for Social Articulation, besides the interviews with key actors. The analysis shows the fragilities on the governance structure thar was stablished and the interruption of the tradition in defending both, multilateralism and social participation, to deal with international agendas on sustainable development, which intensifies after 2018.